Case report: Treatment of anterior cerebral artery aneurysms with combined remodeling technique and flow diverter deployment through a dual lumen balloon catheter - Renieri, Leonardo; Capasso, Francesco; Nappini, Sergio; Laiso, Antonio; Capirossi, Carolina; Limbucci, Nicola (Frontiers in Neurology, 2022)
We present the technical aspects of embolization for two unruptured medium-sized aneurysms of the anterior cerebral artery treated with balloon-remodeling technique and loose coiling of the sac with the final deployment of a 0. 017-compatible flow diverter. Both procedures were performed with dual antiplatelet therapy premedication and under general anesthesia. The anatomy of the two aneurysms was similar with a wide neck and the presence of a collateral artery branching off it, which required the additional use of a compliant balloon in order to retain patency and avoid coil protrusion. After initial coiling, a nitinol flow-diverter was deployed through a coaxial dual lumen balloon microcatheter. Both these interventions encountered no complications, and the patient was discharged on day 2. At 6-month clinical and radiological follow-up, neither patient had neurological deficits, the aneurysms were both completely occluded, nor the stented arteries were patent along with their collateral branches.